Neutrophil-to-lymphocyte-to-albumin ratio as a prognostic marker for mortality in sepsis and septic shock in Vietnam - Nguyen Van Viet Thang; Le Thi Luyen; Nguyen Thi Tuong Vi; Pham Dang Hai (Acute and Critical Care)
Background Sepsis and septic shock are life-threatening global health challenges associated with high mortality rates. Early identification of high-risk patients is critical for improving outcomes. In the present study, the association between the neutrophil-to-lymphocyte-to-albumin ratio (NLAR) and mortality in septic patients was evaluated. Methods A retrospective study was performed at a tertiary hospital in Vietnam. Patients ≥18 years of age diagnosed with sepsis or septic shock based on the Sepsis-3 criteria were included. Exclusion criteria included recent corticosteroid use within 7 days, autoimmune diseases, hematological disorders, and active cancer within 5 years. NLAR was calculated from complete blood counts and albumin levels within the first 24 hours of intensive care unit admission. Receiver operating characteristic (ROC) curves were used to determine the predictive ability of NLAR for in-hospital mortality. Results The present study included 141 patients with a mean age of 72 years. Non-survivors were significantly older with higher rates of mechanical ventilation. NLAR was significantly elevated in non-survivors compared with survivors (median [interquartile range]: 0.88 [0.57–1.24] vs. 0.44 [0.28–0.77], P<0.001). In ROC analysis, the area under the curve for NLAR was 0.70 (P<0.001). Using a cutoff value of 0.56, NLAR showed a sensitivity of 77.8% and a specificity of 61.5% for predicting in-hospital mortality. Conclusions Elevated NLAR on admission was associated with a higher mortality rate in sepsis patients. NLAR could be used as an early prognostic marker for sepsis mortality.